Phaeochromocytoma: back to the basics. Issue 7 (July 2022) - Nimir, Mohammed; Ahmed, Bibi Leila
Abstract: We present a 53-year-old man who was admitted to ITU with shortness of breath and a massive pulmonary haemorrhage, with a history of new-onset hypertension, and unremarkable examination. CT scanning showed an 8 cm mass in the right adrenal gland, suspected to be a phaeochromocytoma (PHEOs). This was further supported by blood tests and avidity on MIBG radiology. Histological examination of the adrenalectomy and nephrectomy specimen showed a circumscribed tumour composed of small nests of small to medium sized, pale to basophilic cells with features suggestive of a phaeochromocytoma with borderline metastatic risk, and a pathological stage of pT2. Stratification of metastatic risk of PHEOs is crucial as those tumours that metastasise have a <50% 5-year survival rate. In addition, risk stratification facilitates management of these tumours, and this can be achieved by employing PASS and GAPP scores, amongst others.